PEMANFAATAN TUMBUHAN DALAM KEHIDUPAN MASYARAKAT SUKU MUYU DIDESA SOA DAN SEKITARNYA, MERAUKE, PAPUA - Susiarti, Siti; Rahayu, Rita D (Research Center for Biology-Indonesian Institute of Sciences, 2003)
Papua possesses high biodiversity and several ethnics.Muyu community at Soa Village, Merauke still has a close relationship with their surroundings, as found in the usage of natural medicine, traditional food and ritual ceremony.A research was conducted at Soa Village and surroundings, Merauke, Papua by open-ended discussion and observation methods.There are 37 species used to cure 26 kinds of diseases as traditional medicines by Muyu Tribe community. Commonly, they use the plants still in wild position, gathered from village surrounding and parts of plant used namely bark, root and leaves.Many kinds of traditional food as staple food like sago (Metroxylon sagu).Wati (Piper methysticum) is used in ritual ceremony.